2016
DOI: 10.1515/jpem-2015-0356
|View full text |Cite
|
Sign up to set email alerts
|

Salivary flow rate, buffer capacity, and urea concentration in adolescents with type 1 diabetes mellitus

Abstract: In adolescents with type 1 DM, hyposalivation at T0 was associated with an increase in urea salivary concentration. At T1, hyposalivation was associated with a reduction in BC, and an increase in salivary urea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stimulated saliva flow rate (SSFR) was evaluated by using a gravimetric method and expressed in mL/minute. SSFR values >0.7 mL/minute were considered to be a normal saliva flow, whereas SSFR values ≤0.7 mL/minute indicated hyposalivation . Xerostomia was assessed from a patient‐centered perspective.…”
Section: Methodsmentioning
confidence: 99%